The Effect of Race and Gender on Attributions of Stalking. (20th January 2020) - Duff, Simon C.; Hay, Jonathan; Kerry, Jessica; Whittam, Alyssa
Abstract : Objective: This study is concerned with examining the impact of the extralegal factors of race and gender in attributions of stalking and motivation in examples of heterosexual, low‐level stalking behavior. Methods: A 4 (race pairing of protagonist and target) × 2 (gender pairing of protagonist and target) between‐ participants design, using a vignette incorporating faces of the protagonist and target, asked participants to identify the extent to which they considered the behavior stalking, the motivation for that behavior, and provide responses to measures of racism and sexism. Results: The results identify that intraracial behavior is considered more like stalking than interracial behavior, that female‐to‐male behavior is considered more like stalking than male‐to‐female, and that gender and race do not impact on the attributed motivations for the behavior. Both racism and sexism do contribute to attributions of stalking. Conclusion: The influence of race on attributions of stalking mirrors that of findings in other areas of crime and is important in understanding decision making.